Mutations in TTC19 cause mitochondrial complex III deficiency and neurological impairment in humans and flies. - Ghezzi, D.; Arzuffi, P.; Zordan, M.; Da Re, C.; Lamperti, C.; Benna, C.; D'Adamo, P.; Diodato, D.; Costa, R.; Mariotti, C.; Uziel, G.; Smiderle, C.; et al. (Nature Genetics, 2011)
Although mutations in CYTB (cytochrome b) or BCS1L have been reported in isolated defects of mitochondrial respiratory chain complex III (cIII), most cIII-defective individuals remain genetically undefined. We identified a homozygous nonsense mutation in the gene encoding tetratricopeptide 19 (TTC19) in individuals from two families affected by progressive encephalopathy associated with profound cIII deficiency and accumulation of cIII-specific assembly intermediates. We later found a second homozygous nonsense mutation in a fourth affected individual. We demonstrated that TTC19 is embedded in the inner mitochondrial membrane as part of two high-molecular-weight complexes, one of which coincides with cIII. We then showed a physical interaction between TTC19 and cIII by coimmunoprecipitation. We also investigated a Drosophila melanogaster knockout model for TTC19 that showed low fertility, adult-onset locomotor impairment and bang sensitivity, associated with cIII deficiency. TTC19 is a putative cIII assembly factor whose disruption is associated with severe neurological abnormalities in humans and flies.